2006
DOI: 10.1080/08039480600583472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a psychiatric intensive care unit in an acute psychiatric department

Abstract: Psychiatric acute units use different levels of segregation to satisfy needs for containment and decrease in sensory input for behaviourally disturbed patients. Controlled studies evaluating the effects of the procedure are lacking. The aim of the present study was to compare effects in acutely admitted patients with the use of a psychiatric intensive care unit (PICU) and not in a psychiatric acute department. In a naturalistic study, one group of consecutively referred patients had access only to the PICU, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 18 publications
1
38
0
6
Order By: Relevance
“…There are, however, studies using PANSS among acute admissions and among patients with bipolar disorders, for example, and serious validity problems have not been reported (80,175). Also, its face validity was good, and in unpublished material from a psychiatric intensive care unit, excellent inter-rater reliability was found in assessing 12 consecutively admitted in-patients (102).…”
Section: Physician Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, studies using PANSS among acute admissions and among patients with bipolar disorders, for example, and serious validity problems have not been reported (80,175). Also, its face validity was good, and in unpublished material from a psychiatric intensive care unit, excellent inter-rater reliability was found in assessing 12 consecutively admitted in-patients (102).…”
Section: Physician Assessmentmentioning
confidence: 99%
“…Also, diagnostic interviews ideally presuppose that substances were not used during the four previous weeks, which rarely is the case among acute admissions with high rates of substance use and short length of hospital stay. Few instruments are tailored for acute care settings (102), which partly may explain why many studies reported routine clinical diagnoses only (Table A1). …”
mentioning
confidence: 99%
“…Nasjonalt senter for erfaringskompetanse innen psykisk helse har bidratt med utdypende litteratursøk om brukeres skjermingserfaringer. Vi fant én semirandomisert studie (4).…”
Section: Kunnskapsgrunnlagunclassified
“…Det gis imidlertid her begrenset vitenskapelig kunnskap om skjermingsmetodens innhold og effekter, spesielt i større utvalg. Det finnes kun én større spesifikk og systematisk behandlingsstudie av skjerming (4). Denne inkluderer fire delstudier om skjerming i forhold til interiør, lukket avsnitt og effekt ved volds-og rusproblematikk.…”
Section: Kunnskapsgrunnlagunclassified
See 1 more Smart Citation